Immunotherapy in breast cancer: Current status and future directions - Basu, Amrita; Ramamoorthi, Ganesan; Jia, Yongsheng; Faughn, Jon; Wiener, Doris; Awshah, Sabrina; Kodumudi, Krithika; Czerniecki, Brian J (Advances in cancer research, 2019)
Breast cancer, one of the leading causes of death in women in the United States, challenges therapeutic success in patients due to tumor heterogeneity, treatment resistance, metastasis and disease recurrence. Knowledge of immune system involvement in normal breast development and breast cancer has led to extensive research into the immune landscape of breast cancer and multiple immunotherapy clinical trials in breast cancer patients. However, poor immunogenicity and T-cell infiltration along with heightened immunosuppression in the tumor microenvironment have been identified as potential challenges to the success of immunotherapy in breast cancer. Oncodrivers, owing to their enhanced expression and stimulation of tumor cell proliferation and survival, present an excellent choice for targeted immunotherapy development in breast cancer. Loss of anti-tumor immune response specific to oncodrivers has been reported in breast cancer patients as well. Dendritic cell vaccines have been tested for their efficacy in generating anti-tumor T-cell response against specific tumor-associated antigens and oncodrivers and have shown improved survival outcome in patients. Here, we review the current status of immunotherapy in breast cancer, focusing on dendritic cell vaccines and their therapeutic application in breast cancer. We further discuss future directions of breast cancer immunotherapy and potential combination strategies involving dendritic cell vaccines and existing chemotherapeutics for improved efficacy and better survival outcome in breast cancer.